Surgical management of traumatic irreducible spondyloptosis of thoracolumbar junction - Nekhlopochyn, Oleksii S.; Verbov, Vadim V.; Cheshuk, Ievgen V.; Vorodi, Milan V. (Ukrainian Neurosurgical Journal, 2021)
Introduction. The thoracolumbar junction is the most common location of traumatic spinal injuries. It accounts for 50-60% of all thoracic and lumbar spine injuries. Spondyloptosis is rather rare, but one of the most severe types of traumatic injury, that is characterized by a severe damage of spinal axis in one or more planes. Traumatic spondyloptosis is classified as reducible and irreducible, depending on the possibility of intraoperative restoration of the spinal axis without resection of the damaged vertebra. Objective. To determine the optimal surgical technique for traumatic irreducible spondyloptosis of thoracolumbar junction. Materials and methods. A retrospective analysis of the patients’ database treated at the Romodanov Neurosurgery Institute, Ukraine was performed over the past 4 years (2017 to 2020) to identify all cases with traumatic irreducible spondyloptosis of the thoracolumbar junction. Results. Treatment outcomes of five patients aged 18 to 52 years (mean age 31.2 years) were analyzed. The minimum period from the moment of injury to surgery was 14 days, the maximum was 3 months and 2 days (on average 42.2 days). At the time of admission all patients had a neurological deficit that corresponds to the functional class A on the American spine injury associatin ASIA scale of severity of spinal cord injury. The TLICS (Thoracolumbar injury classification and severity) score was 8 points. All the patients had the injury of lateral spondyloptosis: in three cases as an isolated displacement only in the coronal plane, in two – as a combined one - in the coronal and sagittal plane. Surgical intervention in all cases was performed from the posterior approach. As a body replacement system in 2 patients, a vertical cylindrical implant (Mesh) was used, in 3 patients - a telescopic body replacing implant. The method of bicortical implantation of pedicle screws was applied. The transpedicular system was strengthened by two cross links of the rod-to-rod type. In all cases the restoration of spinal axis was achieved in both the coronal and sagittal planes. Follow-up examinations were carried out 2, 6 and 12-18 months of the postoperative period. Regression of neurological disorders was registered in two patients, in one case to ASIA B, in the other to ASIA C. Conclusions. Isolated posterior approach has demonstrated high efficacy in the surgical management of traumatic irreducible spondyloptosis of the thoracolumbar junction both in restoring the axis of the spine and in ensuring the stability of fusion.